2014 Computer Games: AI, Animation, Mobile, Multimedia, Educational and Serious Games (CGAMES) 2014
DOI: 10.1109/cgames.2014.6934151
|View full text |Cite
|
Sign up to set email alerts
|

Whale of a crowd: Quantifying the effectiveness of crowd-sourced serious games

Abstract: Abstract-In this paper we analyze several Crowd-Sourced Serious Games (CSSGs), a new genre focused on advancing widely respected causes such as social equality and science. We observe that the general effectiveness of these games has remained largely unknown. Existing performance analyses have been limited to documenting experiences with individual systems. More importantly, existing game analytics approaches are designed for games that provide personal experience and entertainment. In contrast, CSSGs attract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…One study found, analyzing interactions in an online discussion forum, that the content that best explained and predicted learning was related to uncertainty, decisionmaking, time, collaboration and communication (Hernández-Lara, Perera-Lluna, and Serradell-López 2019). In crowd-sourced serious games, three game-play metrics (active users, session counts and session time) were found to be good indicators of productivity by (Tellioglu et al 2014), while team cohesion and psychological safety may be good performance indicators in multiplayer serious games (Mayer et al 2014). Also, behaviors such as avoiding a concept indicated poor performance (Ketamo 2013).…”
Section: Results On Assessment and Student Profilingmentioning
confidence: 99%
“…One study found, analyzing interactions in an online discussion forum, that the content that best explained and predicted learning was related to uncertainty, decisionmaking, time, collaboration and communication (Hernández-Lara, Perera-Lluna, and Serradell-López 2019). In crowd-sourced serious games, three game-play metrics (active users, session counts and session time) were found to be good indicators of productivity by (Tellioglu et al 2014), while team cohesion and psychological safety may be good performance indicators in multiplayer serious games (Mayer et al 2014). Also, behaviors such as avoiding a concept indicated poor performance (Ketamo 2013).…”
Section: Results On Assessment and Student Profilingmentioning
confidence: 99%
“…After the automatic parameter tuning method was introduced, it was much easier for the users to handle complex models. Furthermore, they were able to make improvements, even for the model with a relatively high complexity (59). In the tests of the original approach, the most complex model where the value of the objective function increased had a complexity of 14, which probably also explains why the original approach was better for the low range of complexities.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…Another fascinating application of the crowdsourcing concept is specialized computer games where players can have fun and solve complex scientific problems at the same time [55]. These games are called crowdsourced serious games (this term was first introduced by Tellioglu et al in 2014 [59]) and they have been employed successfully for solving problems that originate from various fields of science. One of the first crowdsourced serious games was FoldIt, which allows players to fold a protein to obtain its tertiary structure.…”
Section: Introductionmentioning
confidence: 99%
“…Cagiltay et al have measured the time spent on reading and responding answers in exploring the effects of game design, on learning outcomes and motivation [29]. Tellioglu et al have used session time as an indicator of productivity in Crowd-Sourced Serious Games [30]. Along with time features, other numerical indicators are frequently examined in serious game analytics.…”
Section: Assessing Serious Games For Learningmentioning
confidence: 99%